Problems of sensorimotor coordination in weightlessness - Bock, Otmar (Brain Research Reviews, 1998)
Previous studies about human sensorimotor coordination in space are inconclusive: it was reported that subjects in weightlessness point too high or too low, too fast or at normal speed, with increased or with normal variability; and that their tracking performance is degraded or normal. A better understanding of human performance in space would be desirable not only from the basic science perspective, but also for operational reasons. We propose a conceptual framework to explain the reported diversity, and to point out avenues for future research. We argue that exposure to weightlessness produces sensorimotor discordance, to which subjects gradually adapt through processes similar to those involved in earthbound adaptation. These processes require substantial information-processing resources in the brain, which may not be easily available during the hectic pace of a space mission. Within this framework, it is not surprising that previous data on sensorimotor performance in space were incongruent, as demand and availability of resources may have differed between missions, or even between subjects. We therefore propose that future work should control resource demand and availability, and study their effects on sensorimotor performance before and during space missions, in order to deconfound their effects from the immediate effects of gravity. A suitable hardware for such research is presented.